Students' Educational Preferences And Occupational Aspirations - Karupiah, Premalatha (2005)
Educational preferences and occupational aspirations of students from three educational stages were investigated. Quantitative data were collected from three samples of approximately 500 students each: form five students in the states of Kedah (excluding Pulau Langkawi) and Penang; first year students In Universiti Sains Malaysia (USM, excluding Kubang Krian branch); and final year students in USM (excluding Kubang Krian branch). Two samples of 15 first year and 15 final year USM students were drawn for qualitative data collection. Quantitative and qualitative data analyses were used to determine factors that influence students' educational preferences and occupational aspirations. The process of making occupational choices spans over many years. Students' educational preferences and occupational aspirations have a reciprocal relationship with one another. The process of occupational choice for students who are in their late adolescence and early adulthood can be divided into four stages: during secondary school; while applying for a bachelor's degree programme; when accepting and enrolling in a bachelor's degree programme; and, prior to the completion of a bachelor's degree programme. The three most important variables influencing students' occupational aspirations found from the quantitative data analysis are students' results, father's education and father's occupation. Other than these variables, gender, ethnicity and mother's education show some influence on students' occupational aspirations. Students' results, father's occupation, father's education and mother's education show influence on students' educational preferences. The analysis of qualitative data on the other hand, yielded results of students, parents' expectations, interests and job opportunity as some of the factors influencing students' educational preferences and occupational aspirations. These four factors were the most common factors mentioned by the first and final year students when interviewed.